Understanding Central Mechanisms of Acupuncture Analgesia Using Dynamic Quantitative Sensory Testing: A Review. (12th May 2013) - Kong, Jiang-Ti; Schnyer, Rosa N.; Johnson, Kevin A.; Mackey, Sean
Abstract : We discuss the emerging translational tools for the study of acupuncture analgesia with a focus on psychophysical methods. The gap between animal mechanistic studies and human clinical trials of acupuncture analgesia calls for effective translational tools that bridge neurophysiological data with meaningful clinical outcomes. Temporal summation (TS) and conditioned pain modulation (CPM) are two promising tools yet to be widely utilized. These psychophysical measures capture the state of the ascending facilitation and the descending inhibition of nociceptive transmission, respectively. We review the basic concepts and current methodologies underlying these measures in clinical pain research, and illustrate their application to research on acupuncture analgesia. Finally, we highlight the strengths and limitations of these research methods and make recommendations on future directions. The appropriate addition of TS and CPM to our current research armamentarium will facilitate our efforts to elucidate the central analgesic mechanisms of acupuncture in clinical populations.